Pengaruh NPM, dan EPS terhadap Harga Saham pada perusahaan sektor industri barang konsumsi di ISSI (perusahaan terdaftar di Bursa Efek Indonesia) - ayu oktamia nugraha (COMPETITIVE, 2022)
The stock price is determined by the supply and demand for the stock it self in a capital market. Whe the higher the puchase of share, the stock price will tend to move up and vice versa. The purpose of this study is to analyze and determine the effect of Net Profit Margin (NPM) and Earning PER Share (EPS) on stock price in industrial sector companies consumer goods in the indonesian sharia stock index (ISSI). In this study using quantitative research with a descriptive approach method. The result of the study show that partially Net Profit Margin (NPM) has no effect on stock price and Earning Per Share (EPS) has no effect on stock price. Meanwhile the research result simultaneously show that Net Profit Margin (NPM) and Earning Per Share (EPS) have no significant effect on stock price.